Faktor Keterlambatan Pada Pasien Kanker Payudara Yang Berobat Di Rsucm Aceh Utara Tahun 2020 - 2021 - Sidrah Nadira, Cut; Rizka, Adi; Humaira, Zahratun (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
cancer is a malignant tumor that begins in the cells in the breast derived from normal cells in the breast can come from the mammary glands, milk ducts, or supporting tissues such as fat. Delay in cancer management can be caused by several things, namely patient delay, doctor or medical personnel's ignorance (doctor delay) and pre-hospital delay (pre-hospital delay). Hospital delay is also a cause of delay in treatment in breast cancer patients, namely the time from the patient's arrival to the point of care until the start of the prescribed medical therapy guidelines. From some of these causes, it can also be grouped the factors that cause cancer delay in the form of predisposing factors, precipitation factors and supporting factors. The purpose of this study was to determine how the factors of delay in breast cancer treatment were treated at the Cut Meutia General Hospital, Aceh Utara. This type of research is descriptive analytic with a retrospective approach. The population in this study were inpatients and outpatients for breast cancer totaling 85 respondents using the Lemeshow formula. The results of the study showed that the value of knowledge was 37 people (43.5%), there was fear as many as 56 people (65.9%), low socioeconomic conditions as many as 40 people (47.1%), affordable health facilities were 64 people (75.3%), had insurance. As many as 77 people (90.6%), had visited alternative medicine as many as 49 people (57.6%) and had family support as many as 65 people (76.5%). The conclusion of this research is the importance of BSE (Breast Self-Examination) education to the public.